Criação e expansão da Rede Federal de Educação Profissional, Científica e Tecnológica : implicações no campo da educação superior - Nascimento, Alexandre Rauh Oliveira (2017)
This study is part of the research on Higher Education Policies, specifically in the discussion about the role of the Federal Institutes of Education, Science and Technology, created in 2008, in the expansion of public higher education in Brazil. The study object is the expansion of the Federal Institutes in Brazil in higher education, from 2008 to 2014, from the thesis which are an alternative form of entry to this level of education. In this sense, the federal institutes would have been constituted from the demands of capital, the reform of the State in the offer of higher education and from institutions that accepted, as a condition for its reconfiguration and growth, an alternative model of higher education.The objective of the study is to analyze the creation and expansion of the Federal Network of Professional and Technological Education and its consequences for the offer of public higher education. The methodology adopted in the study is based on Pierre Bourdieu's theory of the fields of power, under which we settle the understanding of the agents in dispute in the field of higher education, to which the Institutes begin with their reconfiguration, of the necessary scientific capital in the search for affirmation Within the field, and its habitus that the Institutes begin to apprehend. Since the determinations of Capital, in the economic and systemic sense defined by Marx, influence the fields of power, we use Mészáros and Harvey's reference to understand them. This is a research using quantitative analysis, whose source is statistical information from the Synopsis of Higher Education, of qualitative analysis on the documents published by the agents of the elaboration and development of the public policy of vocational and technological education. The results indicate that the expansion occurs under an alternative model to the university of research, whose higher education assumes the attributes of heteronomous, neoprofessional and competitive, considering the manifestations present in the documents that indicate a dispute within the field of higher education and also internally to the Institutes Federal quantitative data indicates a higher expansion, proportionally, to the federal universities in the same period, and the interiorization and diversification are very present elements. At the same time that its vacancies increase, the Institutes show a lower growth in the offer of higher technology courses, a fact that strengthens the thesis of the internal dispute for the courses of higher education that offer. The creation and expansion of the Federal Institutes is part of the expansion of the offer of higher education in Brazil, although in a different model of the research university, contributing through the internalization and democratization of the entrance to public higher education.